Paleomagnetism of the Western Channel Diabase and Associated Rocks, Northwest Territories - Irving, E.; Donaldson, J. A.; Park, J. K. (Canadian Journal of Earth Sciences, 1972)
The stable remanent magnetization of the Western Channel diabase (1325–1785 m.y.) determined at 35 sites has a mean direction of 356, −50 (α 95 = 6°) and a corresponding pole at 9 °N, 115 °W (A 95 = 6°). Studies of rocks bordering the diabase show that this magnetization was acquired at the time of initial cooling. Preliminary results from older sediments, diabase, and porphyry (1770 m.y.) give directions of opposite sign, with corresponding poles in the same general region. These results, and others recently published, allow the path of apparent polar wandering, relative to the Canadian Shield, to be constructed in a preliminary fashion for the middle and earlier Proterozoic. This path, together with that previously obtained by other workers for the late Precambrian, suggests that during the Proterozoic the pole moved through two cycles of a roughly sinusoidal path with a peak-to-peak amplitude of about 90° of arc and a period of several hundred million years.